Virulence Associated Genes and Antibiotic Resistance Profiles in Salmonella Species Isolated from Chickens - Osman , Nabila; Waheed, Dina (International Journal of Poultry Science, 2017)
Background and Objective: Infections due to Salmonella serovars represent a significant public health risk and are economically important for the poultry industry. Genes involved in pathogenesis of Salmonella serovar are clustered within Salmonella pathogenicity islands. Meanwhile, over use of antibiotics in poultry farms has led to an increase in antibiotic resistant Salmonella strains, which can be challenging to control. The present study was conducted to determine antibiotic resistance profiles and to detect the presence of five major pathogenicity islands among Salmonella serovars isolated from chickens in Egypt. Materials and Methods: Samples (n = 930) taken from chicken hearts, livers, caeca, yolk sacs, ovaries and cloacal swabs were collected and used for isolation and serotyping of Salmonella species. Antibiotic resistance was determined using the antibiogram method. The PCR was used for the molecular detection of Salmonella species using primers targeting invA and the pathogenicity islands genes invaE/A, ssaQ, mgtC, spidR and sopB, which are found in the most prevalent Salmonella serovars that present public health concerns. Results: The detection of 30 Salmonella isolates was confirmed by conventional and PCR methods and additional 5 Salmonella isolates were detected only by PCR. Among the isolates, Salmonella Enteritidis, Salmonella Typhimurium, Salmonella Muenster, Salmonella Anatum and Salmonella Virchow were the most prevalent serotypes at 36.7, 26.7, 20, 10 and 6.6%, respectively. The Salmonella serovars showed three antibiotic susceptibility patterns and all prevalent serovars carried the five virulence genes. Conclusion: Salmonella serovars that are pathogenic in chickens and that have public health relevance, including Salmonella Enteritidis, Salmonella Typhimurium and Salmonella Muenster, are circulating in chicken farms in Egypt.